Kebijakan Tembak di Tempat Terhadap Pelaku Kejahatan 3C di Wilayah Hukum Polrestabes Medan - Wamilik Mabel; Syafrudin Kalo; Madiasa Ablisar; M. Ekaputra (DOKTRINA: JOURNAL OF LAW, 2021)
Consumer protection should receive more attention, because foreign investment has become part of Indonesia's economic development, where the Indonesian economy is also related to the world economy which can have negative implications for consumers. This study aims to determine the adoption of the ultimum remedium principle in consumer protection law and to determine the ultimum remedium principle of business actors in consumer protection law. The research method used is a normative juridical research method with secondary data source and analyzed deductively. The research desire to be achieved in consumer protection is to create a sense of security for consumers in meeting the needs of life. It is proven that all consumer protection norms in the Consumer Protection Law have criminal sanctions. The presence of criminal sanctions in consumer protection regulations is a form of ultimum remedium (the last alternative) when resolving consumer protection disputes through other legal channels is not sufficient.